Conversation of easel paintings - Stoner, Joyce Hill; Rushfield, Rebecca Anne (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Conservation of Easel Paintings, 2nd edition provides a much-anticipated update to the previous edition, which has come to be known internationally as an invaluable and comprehensive text on the history, philosophy and methods of the treatment of easel paintings. Including 49 chapters written by more than 80 respected authors from around the world, this volume offers the necessary background knowledge in technical art history, artists' materials and scientific methods of examination and documentation. Later sections of the book provide information about the varying approaches and methods for treatment and issues of preventive conservation, as well as valuable reflections on storage, shipping, and exhibition.. Including exciting developments that have taken place since the last edition was published, the book also covers new techniques of examination, especially MacroXRF scanning and Reflectance Transmission Imagery. Drawing on research presented at recent professional conferences, information about innovative methods for cleaning modern and contemporary paintings and insights into modern oil paints is also included. Incorporating the latest regulations and understanding of health and safety practices and integrating theory with practice throughout, Conservation of Easel Paintings, 2nd edition will continue to be an indispensable reference for practicing conservators. It will also be an essential resource for students taking conservation courses around the world"--
OCLC-licensed vendor bibliographic record.
Keywords: Painting -- Conservation and restoration; ANTIQUES & COLLECTIBLES / Care & Restoration